The relationship of quality of life to the level of ambition in light of some variables among students at the College of Educational Sciences, Mu’tah University - Al-Nuaimi, Fahd Hamad (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to know the relationship of the quality of life with both the level of ambition, as well as to know the differences in the level of both the quality of life and the level of ambition to each of the age, and marital status among female students of the Faculty of Education sciences, Mu’tah University in the Karak region in the Hashemite Kingdom of Jordan, on a sample of (400) female and male students distributed among academic majors were selected randomly, and the quality of life scale, Kazem and Mansi (2006), and the ambition level scale, Barakat (2006) were applied to them. The results of the study showed that the quality of life level was moderate, as it recorded The quality of family life had the highest score, while the quality of time management had the lowest score. The level of ambition was found to be high among the study’s members. The results showed that there was a relationship between all dimensions of quality of life and the level of ambition, and the highest correlation coefficient was with the (quality of family life) dimension, reaching The correlation coefficient is (.43), and the lowest correlation coefficient is with the (time management) dimension, with a correlation coefficient of (.20).. and not Statistical significance at the significance level (α≤0.05) for the quality of life scale and the ambition level scale due to the study variable (marital status), while statistically significant differences were found at the significance level (α≤0.05) in the quality of life and the ambition level due to age, and the differences were in favor of the oldest.